A photothermal system for wastewater disposal and co-generation of clean water and electricity. Issue 1 (February 2022) - Wu, Yuanyuan; Dang, Chenyang; Wu, Jun; Li, Mengli; Chu, Mingming; Gu, Li; Cao, Xuebo
Abstract: Since energy crisis and water shortage become critical issues in increasingly industrialized society, solar-assisted water disposal technologies remain a great challenge. This work investigated solar-driven photothermal disposal of wastewater for simultaneous production of clean water and electricity. This strategy relies on an integrated photothermal and photoelectric film composed of Ag/TiO2 nanoparticles grafted on the surface of carbon nanotubes (CNTs) coated with nickel foam (NF) substrate (Ag/TiO2 @CNTs@NF). The long-wavelength portion in the solar spectrum was employed for high-quality freshwater generation via solar-driven interfacial evaporation (water evaporation rate at 1.48 kg m −2 h −1 ), with a solar-to-water evaporation efficiency of ~96%. The short-wavelength bands were adsorbed for the simultaneous solar-driven oxidation of organic pollutants (oxidation efficiency to methylene blue of ~94.2%) and the generation of electricity (photocurrent of ~228 μA cm −2 ). Therefore, this integrated system can dispose wastewater while achieve pure water and electricity with high utilization efficiency for solar energy. Graphical Abstract: ga1 Highlights: A photothermal wastewater disposal system is designed. The wastewater disposal system co-generates freshwater and electricity. The wastewater disposal system efficiently utilizes full solar spectrum.